The effect of periods and dates on reorganization according to Insolvency Jordanian Law No. 21 of 2018 - Tarawneh, Raed Yassin (Journal of Economic, Administrative and Legal Sciences, 2022)
The preliminary stage is considered as the foundation stone for all the insolvency stages, in that through this stage the insolvency state is confirmed for the debtor and all the basic procedures are taken to apply insolvency law, including applying, verifying the state and causes of insolvency, assigning Insolvency agent, determining the debtor's properties, determining creditors and their categories as well as identifying his debts and verifying them, determining the debtor's acts and the restrictions relating to them, taking all the possible procedures to maintain the insolvency right, in addition to publishing the insolvency decision and other necessary procedures.During this stage, the legislator provided the debtor with a way that he can follow in order to surpass the insolvency case, which is represented by reorganization according to a pre- developed plan, in that when the debtor is about to encounter insolvency during a certain period, the legislator allowed the debtor to prepare a plan that demonstrates a certain mechanism for reorganizing business so that he would avoid insolvency in his economic activity, where all or most creditors accept the plan and is agreed upon by the court.The pre- developed reorganization plan during the preliminary stage is considered as a mechanism that is used by the debtor to protect his economic activity against insolvency, where the debtor and the employees can maintain their income source, whereas the creditors assure obtaining the highest payments of debts and the national income can get more benefits.In this study, the researcher demonstrates the concept of pre-developed reorganization plan, its terms, importance and characteristics in the second chapter. The study demonstrated the mechanism of using, acknowledging, implementing and ending the plan as well as the consequences of that in the third chapter. The preliminary chapter demonstrated the concept of insolvency, the conditions of implementing insolvency law, its characteristics and importance, the mechanism of issuing the insolvency provision, its rules, legal nature and appeal methods. The researcher concluded with a number of results and recommendations, including the importance of insolvency law in protecting the rights of debtors that were overlooked by the cancelled bankruptcy law as well as maintaining the rights of creditors and national income. The study also revealed that the legislator paid attention to the periods of implementing insolvency law.In the light of the results, the study recommended the necessity of organizing the rights of inheritors with regard to using the pre-developed reorganization plan if conditions were available, in addition to other results and recommendations that will be mentioned in the study.
Keywords: duration; date; reorganization; insolvency law; Jordan